2010
DOI: 10.1016/j.brainres.2010.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Developmental characteristics of dendritic spines in the dentate gyrus of Fmr1 knockout mice

Abstract: Fragile X Syndrome (FXS) is the most common form of inherited mental retardation. The neuroanatomical phenotype of adult FXS patients, as well as adult Fmr1 knockout (KO) mice, includes elevated dendritic spine density and a spine morphology profile in neocortex that resembles younger individuals. Developmental studies in mouse neocortex have revealed a dynamic phenotype that varies with age, especially during the period of synaptic pruning. Here we investigated the hippocampal dentate gyrus to determine if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 41 publications
(67 reference statements)
3
58
0
Order By: Relevance
“…Manual counting by estimation without measurements has often been used, leading to experimentator-dependant bias. It should also be noted that the canonical mushroom/thin classification cannot necessarily be extended to all neuronal types (Grossman et al 2010). On the other hand, objective parameters for quantitative spine analysis that do not take into account this classification have already been successfully used (Vecellio et al 2000;Wallace and Bear 2004;Shen et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Manual counting by estimation without measurements has often been used, leading to experimentator-dependant bias. It should also be noted that the canonical mushroom/thin classification cannot necessarily be extended to all neuronal types (Grossman et al 2010). On the other hand, objective parameters for quantitative spine analysis that do not take into account this classification have already been successfully used (Vecellio et al 2000;Wallace and Bear 2004;Shen et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…Spine defects in cortical neurons were detected during early postnatal development (1-3 weeks) and adulthood but not in 4-week-old mice (Galvez and Greenough 2005;Nimchinsky et al 2001). However, in contrast with neocortex, spine abnormalities in the dentate gyrus remain constant during development (Grossman et al 2010). Data obtained on ex vivo and in vitro systems do not consistently corroborate in vivo observations.…”
Section: Spine Dysgenesismentioning
confidence: 91%
“…Mutant mice present increase density of long, immature spines in visual cortex, somatosensory cortex, and hippocampal dentate gyrus Dolen et al 2007;Galvez and Greenough 2005;Grossman et al 2010;Irwin et al 2002;Nimchinsky et al 2001;Restivo et al 2005). Spine defects in cortical neurons were detected during early postnatal development (1-3 weeks) and adulthood but not in 4-week-old mice (Galvez and Greenough 2005;Nimchinsky et al 2001).…”
Section: Spine Dysgenesismentioning
confidence: 97%
“…The analyzed parameters and the described dendritic spine abnormalities vary between different reports. They include in vivo and in vitro studies, as well as analyses of dendritic protrusion and filopodia density, dendritic spine classification, and dendritic arborization (see, eg, McKinney et al, 2005;de Vrij et al, 2008;Gross et al, 2010;Grossman et al, 2010). Some findings are contradictory; for example, several studies have reported significantly increased total dendritic spine density in cultured hippocampal Fmr1 KO neurons as well as in cortex and olfactorial bulb in vivo (Hayashi et al, 2007;Gross et al, 2010;Liu et al, 2011;Scotto-Lomassese et al, 2011), whereas other studies have detected increased numbers of filopodia, but no significant difference in total spine density in the cortex in vivo and in cultured hippocampal neurons (Irwin et al, 2002;de Vrij et al, 2008;Bilousova et al, 2009).…”
Section: Abnormal Dendritic Spine Morphology In Fxsmentioning
confidence: 99%